Сryptocurrency in the system of money laundering - Динту, Валерія Аркадіївна; Динту, В. А.; Дынту, Валерия Аркадиевна; Dyntu, Valeriia A.; Дикий, Олег Вікторович; Дикий, О. В.; Дикий, Олег Викторович; Dykyi, Oleh V. (Riga : Izdevniecība “Baltija Publishing”, 2018)
The target of the article is to study the place of the cryptocurrency in the process of money laundering. The subject of the article is to investigate the ways and means of usage cryptocurrency for money laundering, the possibilities, and limits. Problem’s setting. The authors of the paper have emphasized that despite the broad usage of cryptocurrency all over the world for different kinds of purchasing and transactions, there is no unified position regarding the definition of cryptocurrency, as well as its legal status. Moreover, the aforementioned circumstances trigger the difficulties during the criminal investigation of money laundering by using cryptocurrency. Thus, law informant agencies are facing challenges with the identification of criminals’ personality and the fact of crime commitment. In addition, in the article, the authors articulate the main concept of cryptocurrency: anonymity and decentralization, which engender the main aggro while crime investigation. Methodology. The research is based on an analysis of historical stages of cryptocurrency creation: from Friedrich August von Hayek’s idea of “currency independent from banking and governmental” to the establishment of decentralized currency. Moreover, there were analysed the cases of money laundering where criminals who used cryptocurrency have been identified and press charged. In addition, the comparative methods were used to collate different positions regarding cryptocurrency all over the world and inside Ukraine. The position of the main authorities and organizations regarding the legal status of cryptocurrency was investigated as well. The results of the study revealed that a cryptocurrency is a convenient tool for money laundering because it gives relative anonymity for the owner of the currency, as far as it does not require any personal information about the user and his location. Aforementioned feature minimizes the opportunity for law enforcement agencies to track back the criminal activity and to identify the criminal personality. Furthermore, cryptocurrency transactions are out of the government control because for conducting any transactions by using cryptocurrency, there is no need for their verification by third parties like a bank, governmental authority or nongovernmental organizations. In addition, the user can have more than one account and conduct transactions from different places at the same time.

Метою статті є вивчення місця криптовалюти в процесі відмивання грошей. Предметом статті є дослідження способів та засобів використання криптовалюти для відмивання грошей, можливостей та обмежень. Постановка проблеми. Автори статті підкреслюють, що незважаючи на широке використання криптовалюти в усьому світі для різних видів купівлі та транзакцій, єдиної позиції щодо визначення криптовалюти, а також її правового статусу немає. Крім того, зазначені обставини викликають складнощі під час розслідування кримінальної справи про відмивання грошей з використанням криптовалюти. Таким чином, правоохоронні органи стикаються з проблемами виявлення особистості злочинця та факту вчинення злочину. Крім того, у статті автори формулюють головне поняття криптовалюти: анонімність та децентралізація, які породжують основне агро під час розслідування злочинів. Методологія. Дослідження базується на аналізі історичних етапів створення криптовалюти: від ідеї Фрідріха Августа фон Хайєка про «валюту, незалежну від банківської та урядової» до встановлення децентралізованої валюти. Крім того, були проаналізовані випадки відмивання грошей, у яких були виявлені злочинці, які використовували криптовалюту, та пред’явлені обвинувачення. Крім того, порівняльні методи були використані для порівняння різних позицій щодо криптовалюти в усьому світі та всередині України. Також було досліджено позицію головних органів влади та організацій щодо правового статусу криптовалюти. Результати дослідження показали, що криптовалюта є зручним інструментом для відмивання грошей, оскільки дає відносну анонімність власнику валюти, оскільки не вимагає жодної особистої інформації про користувача та його місцезнаходження. Вищезгадана функція мінімізує можливість правоохоронних органів відстежити злочинну діяльність та встановити особу злочинця. Крім того, операції з криптовалютою знаходяться поза контролем уряду, оскільки для здійснення будь-яких транзакцій з використанням криптовалюти немає необхідності в їх перевірці сторонніми особами, такими як банк, державний орган чи неурядові організації. Крім того, користувач може мати більше одного облікового запису і одночасно здійснювати транзакції з різних місць.
Dyntu V. Сryptocurrency in the system of money laundering / V. Dyntu, O. Dykyi // Baltic Journal of Economic Studies. - Vol. 4. - Issue 5 - Riga : Izdevniecība “Baltija Publishing”, 2018. – Р. 75-81.
Keywords: cryptocurrency; money laundering; criminal investigation; криптовалюта; відмивання грошей; кримінальне розслідування; Research Subject Categories::LAW/JURISPRUDENCE